(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
In contemporary society, there is increasing emphasis on personal appearance and image. Within the rapidly growing cosmetics market, foundation as a core product in base makeup has garnered heightened attention. This study investigates the key factors influencing consumer satisfaction with foundation products, focusing on product knowledge (measured by self-awareness of skincare needs) and personality traits (such as openness to new experiences, enjoyment of life, and preference for variety) a questionnaire survey among 200 consumers with prior foundation usage experience. The survey included three primary constructs: product knowledge, personality traits, and satisfaction with foundation use. Results from factor analysis and correlation analysis using SPSS indicated a significant positive correlation between product knowledge and foundation satisfaction. Personality traits such as novelty-seeking also significantly affect product satisfaction. Another analysis revealed that respondents with high product knowledge and personality traits reported significantly higher product satisfaction. These findings suggest that product knowledge and personality traits affect consumer satisfaction with foundation products.